Kualitas Pelayanan UMDP Analisis Pengaruh Kualitas Pelayanan Terhadap Kepuasan Pelanggan Mahasiswa Universitas Multi Data Palembang - Nathalia Lais; Megawati - (Universitas Multi Data Palembang, 2026)
This study aims to analyze the effect of service quality on student satisfaction at Universitas Multi Data Palembang. The scope of the study covers five dimensions of service quality, namely tangibles, reliability, responsiveness, assurance, and empathy. This research employs a quantitative approach using a descriptive method. Data were collected through questionnaires distributed to 320 student respondents and analyzed using validity and reliability tests, classical assumption tests, multiple linear regression analysis, t-test, and F-test. The results indicate that all dimensions of service quality have a significant effect on student satisfaction, both partially and simultaneously. The conclusion of this study is that service quality plays a crucial role in enhancing student satisfaction, therefore continuous improvement in service quality is essential for higher education institutions.